Accelerating down a Road to Nowhere: On Inventing the Future by Nick Srnicek and Alex Williams. Issue 2 (10th April 2020) - Gildea, Florence
Abstract: In Inventing the Future, Nick Srnicek and Alex Williams implore those on the left not to fear automation but rather to harness it in order to overturn neoliberalism. However, their argument is built upon a controversial philosophy which goes unnamed in the body of the text: accelerationism, the first principles of which would overthrow the very understanding of human nature on which Western democracy has operated for centuries. Their vision also entails a way of doing politics and designing policy which radically differs from representative democracy and grassroots movements as they seek to engineer consent and to form a revolutionary vanguard—not just to overthrow capitalism, but to embark on a journey of continually re‐engineering humanity itself.